Unveiling the Effects of Two Polycyclic Aromatic Hydrocarbons and Two Temperatures on the Trout RTL-W1 Cell Line Expression of Detoxification-Related Target Genes - Margarida Vilaça; Telma Esteves; Rosária Seabra; Eduardo Rocha; Célia Lopes (Journal of Xenobiotics, 2025)
Polycyclic aromatic hydrocarbons (PAHs), prevalent aquatic contaminants, arise from burning fossil fuels, a major source of greenhouse gases driving global warming. PAHs and warmer temperatures individually exert diverse negative effects on aquatic organisms. However, the effects of PAH exposure and/or rising temperature remain largely unknown. Liver in vitro models, like the rainbow trout (Oncorhynchus mykiss) RTL-W1 liver cell line, have been employed to unravel PAH-exposure effects, primarily on cell viability and enzymatic activity. Here, monolayer-cultured (2D) RTL-W1 cells were used to assess the co-exposure effects of temperature (18 and 21 °C) and two PAHs, benzo[a]pyrene (B[a]P) and benzo[k]fluoranthene (B[k]F), at 10 and 100 nM. After a 72 h exposure, the cell density and viability were evaluated using the trypan blue and LDH assays. The mRNA levels of the detoxification-associated genes aryl hydrocarbon receptor (AhR), cytochrome P450 (CYP)1A, CYP3A27, glutathione S-transferase omega 1 (GSTO1), uridine diphosphate–glucuronosyltransferase (UGT), catalase (CAT), and multidrug resistance-associated protein 2 (MRP2) were measured by RT-qPCR. Temperature influenced cell viability and LDH leakage. Both PAHs reduced the cell density and upregulated the mRNA levels of AhR, CYP1A, CYP3A27, and UGT, while GSTO1 and MRP2 were only augmented after the higher B[k]F concentration. Temperature influenced CAT and UGT expression. There was no interaction between temperature and the PAHs. Overall, the results show that B[k]F has more effects on detoxification targets than B[a]P, whereas a temperature increase mildly affects gene expression. The RTL-W1 in 2D seems useful for unravelling not only the liver effects of PAH but also the impact of temperature stress.